Human Resource Management in National Defense Policy:: Reserve Component Management Strategy - Rosmayati, Siti; Arman Maulana (Coopetition : Jurnal Ilmiah Manajemen, 2025)
National Defense Policy plays an important role in maintaining the sovereignty and security of a country, including in the preparation of national defense reserve components. This article discusses the importance of reserve components in facing threats from both within and outside the country. National defense reserve components include various elements, ranging from military personnel, equipment, to defense infrastructure that is ready to be mobilized in emergency situations or large-scale conflicts. This study uses qualitative methods and documentary data collection techniques to analyze the needs and strategies for developing reserve components. Various considerations, such as population size, security conditions, defense strategies, resources, and capacity development, are taken into account in determining the optimal number and needs of reserve components. In addition, the role and function of reserve components in various aspects of national defense activities, as well as follow-up plans for development and training to improve the readiness of reserve components in supporting national security